TINDAK TUTUR ILOKUSI DALAM ACARA KUIS â€œWIBâ€ EPISODE 9 JULI 2018 DI NET TV - Rachmawati, Dian (Universitas Sam Ratulangi, 2018)
The illocutionary acts is a speech act aiming at not only to convey something but also to do something in the form of speech. Speech is not only used to express something because everyone who speaks has a purpose in every speech. The problem studied in this pragmatic research is forms ofÂ illocutionary acts in WIB program in episode 9 July 2018. The purpose of this research is to describe the forms of s illocutionary acts in WIB program in episode 9 July 2018. The method used in this study is qualitative descriptive. Method of data collection using the observation methodÂ by using basic techniques, which is observation technique. Furthermore, observation technique is followed with advanced techniques in the form Â of uninvoluement observation capable of recording, record, and record techniques. The analysis of this research using the method of equalextralingua. Based on the result of the research, it can be concluded that the illocutionary acts in WIB program on July 9, 2018 episode, on Net TV, support Searle concept by discovery five types of illocutionary acts, namely representative, commissive, directive, expressive, and declarative.Keywords: acts of speech, act of speech illocution, quiz WIBÂ